Pemanfaatan Algoritma Apiori Untuk Merekomendasi Produk Pada PT.Centech Metals Engineering - Lubis, Husni; Setiawan, Rifqi; Syahputra, Edy Rahman (Jurnal Sains dan Teknologi, 2023)
− PT.Centech Metals Engineering is a company that was founded in 2000 engaged in the Butterfly Valve, Ball Valve, Air Control Unit, Ductile Valve, High Pressure Pipe Fitting, Inverted Bucket Steam Trap industry. The company address is at Jl. Personality No. 36, Medan, North Sumatra. As an industrial company, Pt.Centech Metals Engineering has a lot of transaction data and customer data that can be utilized to improve business performance and provide better service to customers. So far, the company does not have an application that is able to identify customer purchasing patterns and recommend suitable products for them. The company only has a POS (Point Of Sale) system such as the cashier available at the company and accounting applications. The right product recommendations can help increase customer satisfaction and strengthen customer loyalty. By recommending the right products to customers, companies can increase sales and expand market share. The application of data mining techniques in product recommendations can also help companies optimize product stock. The results of this research are that the Apriori Algorithm is effectively used to recommend products at PT. Centech Metals Engineering is based on the calculation of association patterns between products that have been purchased by previous customers Keywords: Apriori, Data Mining, PT. Centech Metals Engineering